Analysis of the Fungal Diversity and Community Structure in Sichuan Dark Tea During Pile-Fermentation - Yan, Kuan; Abbas, Manzar; Meng, Lina; Cai, Hongbing; Peng, Zhang; Li, Quanzi; El-Sappah, Ahmed H.; Yan, Linfeng; Zhao, Xianming (Frontiers in Microbiology, 2021)
Fungi play pivotal role in development of aroma and physical characteristics of Sichuan dark tea during pile-fermentation. High-throughput sequencing revealed; 7 phyla, 22 classes, 41 orders, 85 families, 128 genera, 184 species in dark tea. Fungal diversity index declined first from W1 to W3 stages of fermentation and then increased exponentially at W4 stage. Barplot and heatmap revealed that Aspergillus, Thermomyces, Candida, Debaryomyces, Rasamsonia, Rhizomocor, and Thermoascus are abundantly found during piling, while Aspergillus is highest among all. Cluster analysis revealed, W4 stage of fermentation is critical time of fungal growth, diversity, and community structure in Sichuan dark tea. This study unravels mechanism and role of fungi on essence and physical characteristics of Sichuan dark tea during pile-fermentation. This study comes under, “Sustainable Development Goals (SDGs)” of UNO to “Establish Good Health and Well-Being”.